2023
DOI: 10.3390/nano13020261
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Oral and Inhalation Acute Toxicity of Nickel Oxide Nanoparticles in Rats

Abstract: Nickel oxide nanoparticles (NiO NPs) have been the focus of many toxicity studies. However, acute toxicity studies that identify toxicological dose descriptors, such as an LC50 or LD50, are lacking. In this paper, the acute toxicity of NiO NPs was evaluated in albino-derived Sprague-Dawley rats through OECD guideline studies conducted by both the oral and inhalation routes of exposure. The animals were assessed for mortality, body weight, behavioral observations, and gross necropsy. Results from previously con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…With this in mind, our 24 h interstitial fluid bioaccessibility data suggest that nickel oxide MPs and NPs may have similar acute inhalation toxicity, with a <1.5-fold difference in release between these samples. This is consistent with the results from our recently published acute inhalation studies in rats [57], with the same nickel oxide (black) samples tested here. The study reported an LC 50 > 8.30 mg/L and >5.42 mg/L, respectively, for nickel oxide MPs and NPs following a 4 h exposure.…”
Section: Inhalation Routesupporting
confidence: 93%
See 1 more Smart Citation
“…With this in mind, our 24 h interstitial fluid bioaccessibility data suggest that nickel oxide MPs and NPs may have similar acute inhalation toxicity, with a <1.5-fold difference in release between these samples. This is consistent with the results from our recently published acute inhalation studies in rats [57], with the same nickel oxide (black) samples tested here. The study reported an LC 50 > 8.30 mg/L and >5.42 mg/L, respectively, for nickel oxide MPs and NPs following a 4 h exposure.…”
Section: Inhalation Routesupporting
confidence: 93%
“…When looking at existing in vivo data, the acute oral LD 50 s for nickel oxide (black) in rats was found to be 9990 mg/kg bw for MPs [57] and >5000 mg/kg for NPs [57], which are within the range of the predicted values noted above (5000 to 12,000 mg/kg bw) based on our bioaccessibility results. The same nickel oxide MP and NP samples were evaluated in Lyons-Darden et al 2023 [57] and in this paper. Published studies with other samples of nickel oxide NPs indicated an LD 50 >1000 and >2000 mg/kg for the Ali, 2019 [58] and Dumala et al 2017 [59] studies, respectively.…”
Section: Oral Routesupporting
confidence: 83%
“…81 However, others reported that inhalation exposure to NiO NPs caused no mortality, reduced body weight only during the first 7 days, which then recovered, and slight to moderate lung discoloration. 82 In addition, NiO NP inhalation only caused minimum inflammation and no changes in mRNA expression of MMP-2, TIMP-2, and type I collagen. 83,84 Low-dose long-term inhalation exposure to NiO NPs only caused mild to moderate chronic toxicity.…”
Section: Pulmonary Effects Of Nio Nps On Ratsmentioning
confidence: 93%